ANALISIS DESAIN PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA PELAJARAN MATEMATIKA SD - Doni Nofrizal; Syafri Ahmad; Salmaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to analyze the design of the application of differentiated learning in the implementation of the Independent Curriculum in Mathematics lessons in Elementary Schools (SD). Differentiated learning as an instructional strategy that adapts learning to the needs, interests, and learning styles of students is expected to accommodate the diversity of student characteristics in the mathematics learning process. The research method used is descriptive qualitative, with a content analysis approach to learning planning documents, interviews with teachers, and observations of learning practices implemented. The results of the study indicate that the application of differentiated learning in the context of the Independent Curriculum can increase the effectiveness of mathematics learning in elementary schools, by providing freedom for teachers to adjust learning materials and strategies according to the level of ability and needs of students. This finding also indicates the importance of developing teacher professionalism in designing and implementing differentiated learning to ensure the achievement of equitable and inclusive educational goals.